Cartografias ontológicas de educadoras do campo da região do Bico do Papagaio-TO: o desvelar do ser-estar da mulher na formação docente em Educação do Campo - Oliveira, Ubiratan Francisco de (2020)
“Ontological Cartographies of Field Educators from Bico do Papagaio” consists of research on the unveiling of the woman's being in the process of teacher education in the Field Education Degree - Arts and Music, at the Federal University of Tocantins, Campus of Tocantinópolis. This process, which involved, among other educational activities, the realization of life history and social cartography workshops as collective processes for producing knowledge about the social and natural phenomena that comprise the totality of the realities that surround us. Therefore, we seek to analyze and understand the Bico do Papagaio region as a space for the materialization of the being of its subjects in the world. We support the theoretical and methodological frameworks of participatory and humanized research conceived in Brazil in the work with popular communities of Carlos Rodrigues Brandão and Paulo Freire in the 1980s. Also in the theory of historical and dialetical materialism, understanding that the being in the world is done in the historical and social materiality of the subjects forged in the class struggle. We started from the assumption of existence a human space, therefore, historical. Thus, the exercise of knowing the Bico do Papagaio from the life trajectories of the families who live in it gives the sense of belonging to the history of the place and, consequently, the understanding of it as a territory in dispute. Dispute over land, water, forest and food that makes the Bico do Papagaio an essential condition for the existence of its subjects. The territory as a space of human existence becomes ontological and, dialectically, space has its ontological meaning in the territory. We seek to understand the ontology of space in the Geography of Milton Santos, Ruy Moreira and Rogério Haesbaert. However, the being of the woman in question is that of the field educator. Therefore, it is necessary to build knowledge about the history of education and its consequences in the formation of a society focused on life in the city to the detriment of life in the countryside, as well as on the role of the school in the construction of the pejorative stereotype of man and woman of the countryside. Faced with this reality, the social movements fighting for land and territory in the countryside have built a pedagogical alternative that seeks to enhance the peoples of the countryside, their cultures and their ways of life. The movement to fight for field education emerges and, from this movement, the concept of integral education in Pedagogy of Alternation in Field Education. The formation of educators based on the epistemology of praxis, on work as a formative principle and on the field as a place of production and reproduction of the existence of their subjects, forges the creation of Field Education Degree and are in the times-spaces of a Field Education Degree that our research was developed. Meeting spaces of different life itineraries that form the Ontological Cartographies of the Field Educators from Bico do Papagaio.